Personal Growth Perempuan Dalam Masa Kehamilan: Scoping Review - Istiqomah, Istiqomah; Surjaningrum, Endang Retno (Jurnal Online Psikogenesis, 2023)
Women have options and opportunities to improve perinatal conditions. This scoping review aims to explore studies related to the personal growth of women during perinatal as a baseline for determining the focus for further research. The search found 10 publications met the inclusion criteria. The identified themes include three main themes, namely: 1) the developmental period of personal growth; 2) influencing factors; and 3) measuring tools used. Perinatal can be viewed as both a normative and a stressful event, in which both conditions have the opportunity to develop personal growth. The characteristics of the subjective experience associated with the event play an important role in the development of personal growth, not the event itself.